Therapeutic radiation and the potential risk of second malignancies. Issue 12 (7th March 2016) - Kamran, Sophia C.; Berrington de Gonzalez, Amy; Ng, Andrea; Haas‐Kogan, Daphne; Viswanathan, Akila N.
Abstract : Radiation has long been associated with carcinogenesis. Nevertheless, it is an important part of multimodality therapy for many malignancies. It is critical to assess the risk of secondary malignant neoplasms (SMNs) after radiation treatment. The authors reviewed the literature with a focus on radiation and associated SMNs for primary hematologic, breast, gynecologic, and pediatric tumors. Radiation appeared to increase the risk of SMN in all of these; however, this risk was found to be associated with age, hormonal influences, chemotherapy use, environmental influences, genetic predisposition, infection, and immunosuppression. The risk also appears to be altered with modern radiotherapy techniques. Practitioners of all specialties who treat cancer survivors in follow‐up should be aware of this potential risk. Cancer 2016;122:1809–21 . © 2016 American Cancer Society . Abstract : Radiation appears to increase the risk of developing secondary neoplasms. This risk appears to be altered by multiple factors.